Question

1.) Simplify (A xor B) + (A xor C) using k-maps, does (A xor B) +...

1.) Simplify (A xor B) + (A xor C) using k-maps, does (A xor B) + (B xor C) have the same k-map.

Homework Answers

Answer #1

Note

########

A xor B is 1 if A and B mismatches ie when (A=0 & B=1 ) or when (A=1 & B=0)

Case 1

#######

For (A xor B) + (A xor C)

When

A=0,B=0,C=0         => (A xor B) + (A xor C) =0+0 =0

A=0,B=0,C=1         =>   0 +1 =1

A=0,B=1,C=0         => 1+ 0 =1

A=0,B=1,C=1         =>   1+1=1

A=1,B=0,C=0         =>   1+1=1

A=1,B=0,C=1         =>   1+0=1

A=1,B=1,C=0         =>    0+1=1

A=1,B=1,C=1         =>   0+0 =0

K Map is as follows

Here we get 3 groups

So the final simplified SOP is

Case 2

##########

For (A xor B) + (B xor C)

When

A=0,B=0,C=0         => (A xor B) + (B xor C) =0 +0=0

A=0,B=0,C=1         => 0+1=1

A=0,B=1,C=0         => 1+1=1

A=0,B=1,C=1         => 1+0 =1

A=1,B=0,C=0         => 1+0=1

A=1,B=0,C=1         => 1+1=1

A=1,B=1,C=0         => 0+1=1

A=1,B=1,C=1         => 0+0=0

So the K Map for (A xor B) + (B xor C) is as follows

Both (A xor B) + (B xor C) and (A xor B) + (A xor C) have same K Map

Know the answer?
Your Answer:

Post as a guest

Your Name:

What's your source?

Earn Coins

Coins can be redeemed for fabulous gifts.

Not the answer you're looking for?
Ask your own homework help question
Similar Questions
Problem 5: Simplify the following Boolean functions, using K-maps: A. ?(?, ?, ?) = ∑(0,1,2,3,5) B....
Problem 5: Simplify the following Boolean functions, using K-maps: A. ?(?, ?, ?) = ∑(0,1,2,3,5) B. ?(?, ?, ?, ?) = ∏(1,3,6,9,11,12,14) Problem 6: Simplify the following Boolean function F, together with the don’t-care conditions A. ?(?, ?, ?) = ∑(0,1,4,5,6), ?(?, ?, ?) = ∑(2,3,7) B. ?(?,?, ?,?) = ∑(0,6,8,13,14), ?(?,?, ?,?) = ∑(2,4,10)
Using K-map to simplify the following Boolean function: F(A,B,C,D) = m(1,3,5,6,7,9,11,12,13,15)
Using K-map to simplify the following Boolean function: F(A,B,C,D) = m(1,3,5,6,7,9,11,12,13,15)
Using K-map to simplify the following Boolean function: F(A,B,C,D) = å m(1,3,5,6,7,9,11,12,13,15)
Using K-map to simplify the following Boolean function: F(A,B,C,D) = å m(1,3,5,6,7,9,11,12,13,15)
Expand the following expression into minterms and then simplify it using K-map. F(A,B,C,D) = BC'D' +...
Expand the following expression into minterms and then simplify it using K-map. F(A,B,C,D) = BC'D' + A'C'D + ACD + BCD + A'BD
Prove that (A xor B) + (A xor C) =  (A xor B) + (B xor C)  ...
Prove that (A xor B) + (A xor C) =  (A xor B) + (B xor C)   using boolean identities.
Simplify the following Boolean functions, using K-maps. Find all the prime implicants, and determine which are...
Simplify the following Boolean functions, using K-maps. Find all the prime implicants, and determine which are essential: (a) F (w, x, y, z) = ? (1, 4, 5, 6, 12, 14, 15) (b) F (A, B, C, D) = ? (2, 3, 6, 7, 12, 13, 14) (c) F (w, x, y, z) = ? (1, 3, 4, 5, 6, 7, 9, 11, 13, 15)
1. Using 2’s complement, convert -(234)10 to binary. 2. Construct a K-Map and simplify this equation:...
1. Using 2’s complement, convert -(234)10 to binary. 2. Construct a K-Map and simplify this equation: X=(ABCD)+(AB’D’)+(B’CD’)+(A’BCD)+(BCD’)+(ABD’)
Find the truth table (function table), SOM, POM, and simplify the expression using K Map approach...
Find the truth table (function table), SOM, POM, and simplify the expression using K Map approach of the following Sigma notation expression: (10 points) f(w,x d y,z)= sum m(0,3,9,10,14,15)
Write a program in C that xor:s two numbers without using the built-in xor bool xor_bit...
Write a program in C that xor:s two numbers without using the built-in xor bool xor_bit ( bool a , bool b ) { // xor two bits , without using ^. } uint32_t xor_word ( uint32_t a , uint32_t b) { // xor two words , without using ^; instead call xor_bit for every bit . } int main () { uint_32 a = 0xaabbccdd ; uint_32 b = 0 x11223344 ; // xor a and b by calling...
Using the algebraic manipulation, Simplify the following expression Y = (A + B)(A + C' )(B'...
Using the algebraic manipulation, Simplify the following expression Y = (A + B)(A + C' )(B' + C' )
ADVERTISEMENT
Need Online Homework Help?

Get Answers For Free
Most questions answered within 1 hours.

Ask a Question
ADVERTISEMENT